Engaging English as a Foreign Language Students in Critical Literacy Practices : The Case of a Teacher at a Private University (2019)
ABSTRACT: This paper describes the process English as a foreign language university students and their teacher underwent when engaging in critical literacy practices. Interviews, focus groups, questionnaires, students’ artifacts, and the teacher’s journal were used to collect data in this study. Findings suggest that when students engage in critical literacy practices, they are prone to reflect on the power they have as agents of social change, while developing language skills. However, teachers should be ready to encounter some resistance from students and to struggle with the incorporation of critical perspectives in their lessons, which is understandable considering the emphasis grammar mastering has traditionally had on language teaching and learning.